Using a mild stimulation protocol combined with clomiphene citrate and recombinant follicle‐stimulating hormone to determine the optimal number of oocytes needed to achieve pregnancy and reduce the concerns of patients. (17th April 2013) - Sugiyama, Rikikazu; Nakagawa, Koji; Nishi, Yayoi; Ojiro, Yuko; Juen, Hiroyasu; Sugiyama, Rie; Kuribayashi, Yasushi
Abstract: Purpose: The purpose of this study was to investigate how many oocytes are needed to achieve an adequate pregnancy rate per 1 oocyte retrieval cycle in mild ovarian stimulation. Methods: This protocol consisted of clomiphene citrate and recombinant‐follicle‐stimulating hormone injection without a gonadotropin‐releasing hormone‐antagonist. From January 2009 through December 2010, there were 1, 227 women who underwent assisted reproductive technologies treatment with mild stimulation at the Sugiyama Clinic. The overall pregnancy rate per single oocyte retrieval cycle was evaluated using both fresh and cryopreserved‐and‐thawed embryos according to the retrieved oocyte number. Results: According to the retrieved oocyte number, a total of 1, 227 cycles were divided into 4 groups: group A (the oocyte number <4; 433 cycles), group B (the oocyte number = 4, 5; 317 cycles), group C (the oocyte number = 6, 7; 206 cycles), and group D (the oocyte number ≥8; 271 cycles). The overall pregnancy rates for groups A, B, C, and D were 22.2, 42.9, 52.4, and 56.0 %, respectively, the rates for groups C and D were significantly higher than that for group A ( p < 0.01). Conclusions: The optimal number of retrieved oocytes proved to be between 6 and 7 for the patients who received our milder stimulation protocol and experienced no reduction in their overall pregnancy rate.